Defining Mediation & Mediation Success: The Role of Mediation in Facilitating Conflict Resolution and Negotiation (Journal of Advances and Scholarly Researches in Allied Education, 2012)
When parties in conflict are in no position to negotiatedirectly, but have a genuine will to overcome the situation they are in, theytend to seek a person or institution to help them reach a satisfactoryagreement. Mediation, in itself, does not have to be imposed by third parties(although this might be suggested or induced), but should always be freelyaccepted by the parties in conflict.  Mediationis, more than anything, a communication exercise that seeks to conciliate theinterests of the parties in dispute, assisting them to find a way out, butwithout imposing a solution upon them from outside. The person that  mediates a conflict and the parties’interests must have a broad understanding of the conflict and respective interests, must have certain personalitytraits  (honesty, impartiality,flexibility, empathy, patience, etc.) and must be a master  of certain well known and widely promotedmediation skills and techniques  (paraphrasing,summarising, prioritising, starting with assumable objectives,  temporarily keeping a distance in order togenerate new ideas and focuses, clarifying needs and interests, resituating the conflict, broadening thescope,  moving outside of the usualconceptual framework, emphasising common values, breaking down the problem, helping the parties to makesmall  concessions, etc.) that can leadto new approaches, break deadlocks, open new dialogues, achieve more activeparticipation and help to find a solution in which all of the parties come outwinning.  Mediation intervenes in theactors’ conducts, in order for them to agree to matters of mutual benefit, andnot in terms of structures, which should be a derivation of the agreements the parties reach. The target is to modifythe  relations between the parties inconflict. This also has its stages and moments (initial contacts, data collection, the establishment of the rules ofplay, process  design, the identificationof agreements and incompatibilities, the visualisation of hidden agendas,reformulation, the generation of options and the  achievement of agreements and compromises),and forms an integral part of  any negotiationprocess.